Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Please help! Simplify the following expression by combining like-terms.

Please Help Simplify The Following Expression By Combining Liketerms class=

Sagot :

Step-by-step explanation:

[tex] = 4x - 8y + 6 {x}^{2} + 3x - 5y[/tex]

[tex] = 6 {x}^{2} + (4x + 3x) + ( - 8y - 5y)[/tex]

[tex] = 6 {x}^{2} + 7x - 13y[/tex]

The answer is B.

Answer:

b.) 6x² + 7x - 13y

Explanation:

Given Expression

= 4x - 8y + 6x² + 3x - 5y

collect like terms

= 6x² + 4x + 3x -8y - 5y

combine similar terms

= 6x² + 7x - 13y